Beyond Compliance: Constructing a Maqāṣid-Based Framework for Shariah Governance in Ethical Islamic Finance - Umar, Rahmawati; Wahab, Abdul (Indonesian Journal of Advanced Research, 2025)
This article examines the weaknesses of the Shariah Governance (SG) framework that focuses too much on formal legal compliance, thus neglecting the objectives of Islamic ethics (maqāṣid al-sharīʿah). With conceptual and normative approaches, this study proposes a Maqāṣid-Based Shariah Governance (MSG) framework that emphasizes value-based ethical governance. MSG includes elements such as value instillation, ethical oversight, a dynamic fatwa process, and maqāṣid-based performance indicators. This article also integrates ESG principles with maqāṣid to promote sustainable and ethical Islamic finance.